Experimental study for thermal methane cracking reaction to generate very pure hydrogen in small or medium scales by using regenerative reactor - Yousefi, Mahdi; Donne, Scott (Frontiers in Energy Research, 2022)
Nowadays, hydrogen potentially plays a crucial role in the clean, secure and affordable energy scenarios of the future, and there is a significant interest in the small scale hydrogen generation. Non-catalytic thermal methane cracking (TMC) is an alternative process for hydrogen manufacturing along with the traditional commercial processes. Supplying the heat of reaction and reactor blockages are two fundamental challenges for a non-catalytic reaction way [1]. A regenerative reactor could be a part of a solution to overcome these obstacles. A reaction experimental study has been developed in a regenerative reactor environment between 850 to 1170 ˚C and atmospheric pressure. The results reveal that the storage medium is a bed for carbon deposition and successfully supplies the heat of the reaction, and 99.7 % hydrogen yield was obtained at higher temperatures (more than 1150 ˚C). Results also indicated that the reaction rate at the beginning of the reactor is much higher, and the temperature dependence in the early stages of the reaction is considerably higher. However, after reaching a particular concentration of hydrogen at each temperature, the influence of temperature on the reaction rate decreases and is almost constant. The type of produced carbon in the storage medium and its possible catalytic effect on the reactions were also investigated. Results showed that carbon black had been mostly formed but in different sizes from 100 nm to 2000 nm. By increasing the reactor temperature, the size of the generated carbon was decreased. Pre-produced carbon in the reactor did not affect the production rate and is almost negligible at more than 850 ˚C.